Vagus Nerve Stimulation as a Treatment for Catatonia: A Hypothesis - Zilles, David (Frontiers in Psychiatry, 2019)
Background: Catatonia is a syndrome comprising psychomotor, behavioral and autonomous symptoms which may occur in the context of severe schizophrenic, affective, and other mental disorders or medical conditions. Treatment options include high dose benzodiazepines (lorazepam) and electroconvulsive therapy (ECT) with some evidence for the effectiveness of glutamate antagonists. However, due to a lack of randomized controlled studies in this severely ill population, evidence base is weak. Methods: On occasion of the case of a patient with treatment resistant catatonia in schizoaffective disorder, we developed the hypothesis of vagus nerve stimulation (VNS) being a potential therapy for treatment resistant catatonia. Results: Based on a selective literature search, we found a remarkable overlap of the pathophysiology of catatonia on the one hand and the putative mechanisms of action of VNS on the other hand in several domains: functional brain imaging, involved neurotransmitter systems, clinical, and theoretical. We thus decided to use VNS as a single subject clinical trial. During the one-year-follow-up, we observed a fluctuating, but ultimately marked improvement of both catatonic symptoms and general psychopathology. Conclusions: We assume there is a sufficient hypothetical corroboration for the potential effectiveness of VNS as a long-term treatment in predominantly catatonic syndromes. This hypothesis could be tested in proof-of-concept clinical trials.